2005
DOI: 10.1292/jvms.67.1207
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Function Using Pulsed Tissue Doppler Imaging in Healthy Dogs and Dogs with Spontaneous Mitral Regurgitation

Abstract: ABSTRACT. Pulsed tissue Doppler imaging (pulsed TDI) has been demonstrated to be useful for the estimation of left ventricular (LV) systolic and diastolic functions in various human cardiac diseases. The objectives of this study were to investigate the relationship between pulsed TDI and LV function by using cardiac catheterization in healthy dogs and to evaluate the clinical usefulness of pulsed TDI in dogs with spontaneous mitral regurgitation (MR). The peak early diastolic velocity (E'), peak atrial systoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 47 publications
12
48
1
7
Order By: Relevance
“…Many reports have shown that E/Ea is a good index for the estimation of LAP and left ventricular filling pressure. [12][13][14][26][27][28] In the present study, E wave and E/Ea were significantly decreased after the administration of furosemide (Figs 6 and 7). This result suggests that E wave and E/Ea can be used for the evaluation of furosemide treatment at a high dosage, and monitoring of the reduction of LAP in the short term.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Many reports have shown that E/Ea is a good index for the estimation of LAP and left ventricular filling pressure. [12][13][14][26][27][28] In the present study, E wave and E/Ea were significantly decreased after the administration of furosemide (Figs 6 and 7). This result suggests that E wave and E/Ea can be used for the evaluation of furosemide treatment at a high dosage, and monitoring of the reduction of LAP in the short term.…”
Section: Discussionmentioning
confidence: 50%
“…[12][13][14] Few studies have evaluated the LAP after the administration of furosemide with comparison between IV and PO routes. In the present study, our findings indicate that LAP is significantly lowered by furosemide in experimental cases, and the 2 administration routes have almost the same pharmacological actions in LAP-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually thinner, elongated, and often prolapsed (Figure 11-25). Second, the LV systolic dysfunction seems to be more pronounced in larger breeds than in small dogs, with a marked increase of the ESVI [19,55]. Atrial fibrillation is often observed [55].…”
Section: Dmvd In Large Breed Dogsmentioning
confidence: 99%
“…The proposed threshold values for identification of elevated LAP (>20 mm Hg) in dogs with DMVD are E >1.25 m/s, E/E′ >12, IVRT <45 ms, and E/IVRT >2.5 [22,55].…”
Section: Evaluation Of the Left Atrial Pressurementioning
confidence: 99%
“…Parameters obtained with tissue Doppler imaging (TDI) have been shown to be more independent of pre-and after-load than classic haemodynamic Doppler measurements and can be used to quantify regional myocardial function accurately and more objectively (Sohn et al, 1997;Firstenberg et al, 2001;Nagueh et al, 2001). Pulsed TDI of the mitral annulus and myocardial wall has been suggested as a means to assess systolic and diastolic left ventricular (LV) function in human and veterinary medicine (Oki et al, 1999;Chetboul et al, 2005;Teshima et al, 2005;Chetboul et al, 2006;O'Sullivan et al, 2007). The Tei index, a new parameter to assess myocardial performance, has been proposed for the assessment of global cardiac performance (systolic and diastolic function) in a wide variety of congenital and acquired cardiac abnormalities (Dujardin et al, 1998;Bruch et al, 2002;Haque et al, 2002;Harjai et al, 2002;Gaibazzi et al, 2005;Dyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%